Performance Analysis of Two for One (TFO) Machine on Production Efficiency in Textile Industry using OEE and FMEA (Science and Technology (SciTech), 2023)
The effects of the COVID-19 pandemic are still being felt by several textile and textile product industries. Due to this, the textile industry has to struggle to survive the impact of COVID, compounded by the scarcity of raw materials. One of the things that can be done is to improve the quality and increase the productivity of the company. Currently, productivity measurement in the company is only limited to machine efficiency, which can be challenging as the indicators may not be accountable. This study aims to measure the level of productivity and performance using the Overall Equipment Effectiveness (OEE) and Failure Mode Effect Analysis (FMEA) tools as means to further analyze the priority of improvements that need to be made. After conducting the performance analysis using OEE, it is evident that the TFO department has a score of 65.46%. This figure indicates that there is still a significant opportunity for improvement to reach the desired performance target. FMEA is a suitable tool for providing recommendations to the company for improvement. The results of FMEA indicate that the main issue with the highest score of 224 is the lack of employees. With these results, it is expected that the company can increase the number of employees according to the workload analysis so that OEE can improve, and the performance of the TFO department can meet the desired expectations.